2005
DOI: 10.1021/la0469147
|View full text |Cite
|
Sign up to set email alerts
|

Tethered or Adsorbed Supported Lipid Bilayers in Nanotubes Characterized by Deuterium Magic Angle Spinning NMR Spectroscopy

Abstract: 2H solid-state NMR experiments were performed under magic angle spinning on lipid bilayers oriented into nanotubes arrays, as a new method to assess the geometrical arrangement of the lipids. Orientational information is obtained from the intensities of the spinning sidebands. The lipid bilayers are formed by fusion of small unilamellar vesicles of DMPC-d54 inside a nanoporous anodic aluminum oxide, either by direct adsorption on the support or by tethering through a streptavidin/biotin linker. The results sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…These processes range from passive uptake of small molecules to active processes such as endocytosis and cell signaling. Given the range and importance of lipid membrane chemistry, considerable effort has been made to develop model phospholipid bilayers supported on a range of substrates. A common approach to forming model membrane systems is the assembly of a phospholipid bilayer on a glass or silica substrate prepared either by fusion of phospholipid vesicles or Langmuir–Blodgett/Langmuir–Schaefer deposition of phospholipids on planar supports. , Planar-supported phospholipid bilayers have been employed in a variety of experiments for assessing bilayer structures, , investigating membrane interactions with peptides and proteins, , and providing membrane-like supports for ligand binding experiments and biosensing. ,, To increase the surface area for spectroscopic characterization of these structures, supported lipid bilayers have also been deposited by vesicle fusion onto the interior surfaces of porous alumina membranes and porous silica particles. , …”
Section: Introductionmentioning
confidence: 99%
“…These processes range from passive uptake of small molecules to active processes such as endocytosis and cell signaling. Given the range and importance of lipid membrane chemistry, considerable effort has been made to develop model phospholipid bilayers supported on a range of substrates. A common approach to forming model membrane systems is the assembly of a phospholipid bilayer on a glass or silica substrate prepared either by fusion of phospholipid vesicles or Langmuir–Blodgett/Langmuir–Schaefer deposition of phospholipids on planar supports. , Planar-supported phospholipid bilayers have been employed in a variety of experiments for assessing bilayer structures, , investigating membrane interactions with peptides and proteins, , and providing membrane-like supports for ligand binding experiments and biosensing. ,, To increase the surface area for spectroscopic characterization of these structures, supported lipid bilayers have also been deposited by vesicle fusion onto the interior surfaces of porous alumina membranes and porous silica particles. , …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the new AAO-supported bilayers retain many biophysical properties of unsupported lipid vesicles (19,20), and they are suitable for aligning membrane proteins for high-resolution multidimensional solidstate NMR studies (17). Detailed NMR (17,18,21,22) and DSC (19,20) studies provided further characterization of the biophysical properties of such nanotubular bilayers. Specifically, 31 P NMR studies of POPC (1-palmitoyl-2-oleoyl-snglycero-3 phosphocholine) bilayers absorbed into AAO nanopores indicated that some portions of the bilayer surface were inaccessible to Pr 31 shift reagent when the bilayer was maintained above the main phase transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Anodic oxidation of aluminum produces γ-alumina with a reproducible pore size in the submicrometer range, high pore density, and a narrow pore size distribution. Several laboratories reported feasibility of depositing phospholipid layers on the cylindrical walls of AAO pores ( ). The tubular lipid bilayers cover pore walls over their entire length.…”
mentioning
confidence: 99%